Challenge is in the eye of the beholder: Exploring young athlete's experience of challenges on the talent pathway. Issue 10 (19th May 2022) - Williams, Graham G.; MacNamara, Áine
ABSTRACT: The journey of young athletes on the talent pathway in sport has been identified as non-linear. Central to this has been the influence of challenging experiences, yet little is known on the experiences of currently young athletes during the challenge, particularly in the early years of the talent pathway. The purpose of this study was to explore the experiences of young athletes as they negotiated their self-identified most difficult challenge. Eight participants were purposefully sampled based on their involvement in the early years of a talent pathway and their status as currently young athletes. Individual semi-structured interviews were conducted at two time points separated by five months. Data was analysed via thematic analysis. Participants identified the bespoke nature and impact of their most difficult challenge, a range of psychobehavioural skills and diverse social support to engage with and embrace their most difficult challenge and the influence of their most difficult challenge on the preparation for future challenges. Talent pathway stakeholders should be cognisant of the preparation, individualisation and reflection processes required to optimise talent development via challenges. Specifically, young athletes should be supported in skilfully deploying psychobehavioural skills, assisted by key personnel who purposefully aid in navigating the most difficult challenges.